Tantangan dan Peluang Maksimalisasi Laba dalam Perspektif Islam: Studi Kasus Pelaku Usaha di Pulau Bengkalis - Azriani, Sri; Rahmadiah, Ika Triayu; Hendra, Joni (Yayasan Rahmat Islamiyah, 2024)
This study aims to analyze the challenges and opportunities faced by business owners in Bengkalis Island in maximizing profit according to the principles of Islamic economics. In Islam, profit maximization must adhere to ethical values, justice, and lawful practices, requiring entrepreneurs to balance business interests with Shariah demands. This research employs a qualitative method with a case study approach, where data were collected through in-depth interviews and observations of business owners in Bengkalis Island. The findings reveal that the main challenges include limited market access, lack of Islamic economic literacy, and price fluctuations of raw materials. However, there are also significant opportunities, such as increasing demand for halal products and government policy support. The conclusion emphasizes the need for a deeper understanding of Islamic economics in business strategies and strengthening Shariah literacy to fully capitalize on existing market opportunities.